Finding nascent proteins the right home - Kramer, Günter; Guilbride, D. Lys; Bukau, Bernd (Science, 2015)
Cells must deliver the thousands of polypeptides they synthesize every minute to various specific subcellular locations. Precisely how this happens has been a topic of intense research, and some controversy, for the past 20 years, as critical components of the translation and translocation machineries - ribosomes and the signal recognition particle (SRP) - do not confer full target discrimination.